Novel cinnamon-laden nanofibers as a potential antifungal coating for poly(methyl methacrylate) denture base materials - Ribeiro, Juliana Silva; Bordini, Ester Alves Ferreira [UNESP]; Pereira, Gabriel Kalil Rocha; Polasani, Rohitha Rao; Squarize, Cristiane Helena; Kantorski, Karla Zanini; Valandro, Luiz Felipe; Bottino, Marco Cícero (Springer Nature, 2022)
Objectives: To modify the surface of denture base material by coating it with cinnamon-laden nanofibers to reduce Candida albicans (C. albicans) adhesion and/or proliferation. Materials and methods: Heat-cured poly(methyl methacrylate) (PMMA) specimens were processed and coated, or not, with cinnamon-laden polymeric nanofibers (20 or 40 wt.% of cinnamon relative to the total polymer weight). Scanning electron microscopy (SEM) and Fourier-transform infrared spectroscopy (FTIR) analyses of the nanofibers were performed. Antifungal activity was assessed through agar diffusion and colony-forming unit (CFU/mL) assays. Representative SEM morphological analysis was carried out to observe the presence/absence of C. albicans on the fibers. Alamar blue assay was used to determine cell toxicity. Analysis of variance and the Tukey’s test were used to analyze the data (α = 0.05). Results: SEM imaging revealed nanofibers with adequate (i.e., bead-free) morphological characteristics and uniform microstructure. FTIR confirmed cinnamon incorporation. The cinnamon-laden nanofibers led to growth inhibition of C. albicans. Viable fungal counts support a significant reduction on CFU/mL also directly related to cinnamon concentration (40 wt.%: mean log 6.17 CFU/mL < 20 wt.%: mean log 7.12 CFU/mL), which agrees with the SEM images. Cinnamon-laden nanofibers at 40 wt.% led to increased cell death. Conclusions: The deposition of 20 wt.% cinnamon-laden nanofibers onto PMMA surfaces led to a significant reduction of the adhesive and/or proliferative ability of C. albicans, while maintaining epithelial cells’ viability. Clinical relevance: The high recurrence rates of denture stomatitis are associated with patient non-adherence to treatments and contaminated prostheses use. Here, we provide the non-patients’ cooperation sensible method, which possesses antifungal action, hence improving treatment effectiveness.
Keywords: Candida albicans; Cinnamomum verum; Denture stomatitis; Electrospinning; Nanofibers